The effect of plyometric exercises on the muscular power of the lower and upper extremities and the skills of the smashing blow and the blocking wall in the junior volleyball players (Journal of the College of Basic Education, 2022)
The research included five chapters:The first chapter included the introduction and the importance of the research, as the introduction dealt with that physical education has a respectable position among the various sciences that serve the individual and society and contribute to its construction and happiness. Physical education did not reach this position until after its philosophy had developed.